From comparative history to multi-situated research: On the footsteps of African sports managers - (:unkn) unknown (My University, 2020)
This paper shows the interest of associating multi-situated approach and comparative history, in order to nuance historical narrative and helping new analytical trails emerge. Following transnational actors – outside of State diplomacy – is allowed by using « shadow archives » in order to nuance the comparative analysis between States. This paper is an example of crossed use of multi-situated data, located in West Africa, Europe and the United States: life-interviews and archives from a various range of fonds (State, international organizations and universities). Observing the connections between these varied data allows one to trace back the flows which developed between and beyond State-level. This methodology is exemplified through a case study of Ghanaian and Ivoirian sport specialists’ biographies following the independence.
Keywords: African Research